2012
DOI: 10.1021/bm3000716
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Multi/Pluri-Potent Stem Cell Fate by Electrospun Poly(l-lactic acid)-Calcium-Deficient Hydroxyapatite Nanocomposite Mats

Abstract: In this study, we investigated whether multipotent (human-bone-marrow-derived mesenchymal stem cells [hBM-MSCs]) and pluripotent stem cells (murine-induced pluripotent stem cells [iPSCs] and murine embryonic stem cells [ESCs]) respond to nanocomposite fibrous mats of poly(L-lactic acid) (PLLA) loaded with 1 or 8 wt % of calcium-deficient nanohydroxyapatite (d-HAp). Remarkably, the dispersion of different amounts of d-HAp to PLLA produced a set of materials (PLLA/d-HAp) with similar architectures and tunable me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 55 publications
3
82
1
Order By: Relevance
“…The osteogenic induction capability of these HAp-containing nanofibers, even in the absence of osteogenic factors, has been well-documented previously [20,21]. It was found that incorporation of HAp at an amount of as low as merely 1 wt% was effective to activate the molecular signals for the onset of osteodifferentiation mechanisms of multi/pluri-potent stem cells [47]. In the present study, we devised HAp/Col/CTS electrospun …”
Section: Discussionmentioning
confidence: 62%
“…The osteogenic induction capability of these HAp-containing nanofibers, even in the absence of osteogenic factors, has been well-documented previously [20,21]. It was found that incorporation of HAp at an amount of as low as merely 1 wt% was effective to activate the molecular signals for the onset of osteodifferentiation mechanisms of multi/pluri-potent stem cells [47]. In the present study, we devised HAp/Col/CTS electrospun …”
Section: Discussionmentioning
confidence: 62%
“…Although embryonic SCs present interesting properties, such as the ability to differentiate into hundreds of other cell types, the bioethical aspects involved in the study of these cells, especially for human embryos, have hindered advances in this field and research has thus been focused on adult SCs [1,[10][11][12] . Adult SCs can be obtained from adult specialized tissues, such as bone marrow [13][14][15][16] , skin [17,18] and fat [19][20][21][22][23] , where they likely act to renew cell populations and maintain tissue homeostasis, or help to repair the tissue in case of injury [18,24,25] . Even though adult SCs can be obtained from less ethically concerning sources, they have some limitations compared to embryonic SCs, such as more limited lifespan and differentiation potential [1,11,24,26] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DSC analyses and uniaxial tensile tests were performed on the PFM, in order to investigate the influence of GaOS and DADS on the thermal and mechanical properties of the produced fibers, respectively. Indeed, it is well known that the scaffold topographical, chemico-physical, and mechanical properties can play a pivotal role in the stem cell differentiation towards specific phenotypes as well as on the preservation of their stem cell status [54,55], even if the underneath mechanisms of this phenomenon (mechanotransduction) have not been fully comprehended and identified. The glass transition (T g ), melting (T m ), cold crystallisation (T cc ) temperatures, the melting (ΔH m ) and cold crystallization (ΔH cc ) enthalpies, and the crystallinity degree (χ), related to the first and the second heating scans, are summarised in Table 2.…”
Section: Resultsmentioning
confidence: 99%